2013
DOI: 10.7763/ijfcc.2013.v2.161
|View full text |Cite
|
Sign up to set email alerts
|

Social Network Analysis and Information Propagation: A Case Study Using Flickr and YouTube Networks

Abstract: Social media and Social Network Analysis (SNA)acquired a huge popularity and represent one of the mostimportant social and computer science phenomena of recentyears. One of the most studied problems in this research area isinfluence and information propagation. The aim of this paper isto analyze the information diffusion process and predict theinfluence (represented by the rate of infected nodes at the end ofthe diffusion process) of an initial set of nodes in two networks:Flickr user’s contacts and YouTube vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Furthermore, comparing the cascade effect between Digg and Twitter, researchers have observed that Digg's dense network leads to faster but limited spread of information, while Twitter's lose network created a slower but a wider spread of information. Thus, confirming that network structures can profoundly influence reach [29,30].…”
Section: Three Paradigms To Interpret Anti-vaccination Movementmentioning
confidence: 56%
“…Furthermore, comparing the cascade effect between Digg and Twitter, researchers have observed that Digg's dense network leads to faster but limited spread of information, while Twitter's lose network created a slower but a wider spread of information. Thus, confirming that network structures can profoundly influence reach [29,30].…”
Section: Three Paradigms To Interpret Anti-vaccination Movementmentioning
confidence: 56%
“…It is worthwhile remarking that Theorem 4.5 also sheds a useful insight that for the IMP with a general large and well-connected network  (not necessary to be complete) with high arc probabilities 𝜋 ij , the SCNA and INA can be expected to effectively reduce the sizes of the live-arc graphs and SMCLP formulation (3). Indeed, a well-connected network is likely to contain large complete subgraphs.…”
Section: Complete Network Under the Icmmentioning
confidence: 94%
“…Indeed, to simplify the problem formulation, we can remove variable z 𝜔 1 and its corresponding reachability constraint in (3b) and add the objective coefficient of variable z 𝜔 1 into that of variable z 𝜔 2 . In general, for any given two strongly connected nodes i 1 , i 2 ∈  in a live-arc graph  𝜔 (i.e., there exists a directed path from node i 1 to node i 2 in  𝜔 and vice versa), we can remove one of the two variables and the corresponding reachability constraint in (3b) from formulation (3). Notice that for a given SCC in a live-arc graph, as all of its nodes are strongly connected, we can recursively apply the above argument until there remains only a single variable and a single constraint in (3b) associated with this SCC.…”
Section: Strongly Connected Nodes Aggregationmentioning
confidence: 99%
See 2 more Smart Citations